Homework Practices of English and Non-English–Speaking Parents. (July 2014) - Thelamour, Barbara; Jacobs, D'Andrea L.
This study compared the homework practices of English-speaking and non-English–speaking parents. Using a national data set of 7, 992 students across ages and ethnicities, the frequency and type of homework practices were investigated. Statistical analysis revealed significant (though small) differences between the overall homework practices between the groups of parents. There were also differences between the types of homework strategies parents employed, with English-speaking parents more likely to provide a place for homework and helping with homework and non-English more likely to check for homework completion. The results challenge the notion that nondominant parents are less involved in their children's homework.